2022
DOI: 10.1002/advs.202201214
|View full text |Cite
|
Sign up to set email alerts
|

Future Prospects for Clinical Applications of Nanocarbons Focusing on Carbon Nanotubes

Abstract: Over the past 15 years, numerous studies have been conducted on the use of nanocarbons as biomaterials towards such applications as drug delivery systems, cancer therapy, and regenerative medicine. However, the clinical use of nanocarbons remains elusive, primarily due to short‐ and long‐term safety concerns. It is essential that the biosafety of each therapeutic modality be demonstrated in logical and well‐conducted experiments. Accordingly, the fundamental techniques for assessing nanocarbon biomaterial safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 164 publications
(189 reference statements)
0
4
0
Order By: Relevance
“…For example, the potential toxicity of nanocarbons is a crucial aspect to address for their safe use in biomedical applications. 34 Their toxicity can vary depending on several factors, including the specic type of nanocarbon (e.g., carbon nanotubes and graphene), dimensions (e.g., length and diameter), surface characteristics (e.g., functionalization and charge), and the biological system that they interact with. 35 Some studies have indicated that certain forms of nanocarbon, particularly long and rigid carbon nanotubes, may induce inammation or cellular damage under certain conditions.…”
Section: Biosafety Of Carbon Nanomaterials: Crucial For Biomedical Ap...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the potential toxicity of nanocarbons is a crucial aspect to address for their safe use in biomedical applications. 34 Their toxicity can vary depending on several factors, including the specic type of nanocarbon (e.g., carbon nanotubes and graphene), dimensions (e.g., length and diameter), surface characteristics (e.g., functionalization and charge), and the biological system that they interact with. 35 Some studies have indicated that certain forms of nanocarbon, particularly long and rigid carbon nanotubes, may induce inammation or cellular damage under certain conditions.…”
Section: Biosafety Of Carbon Nanomaterials: Crucial For Biomedical Ap...mentioning
confidence: 99%
“…For example, the potential toxicity of nanocarbons is a crucial aspect to address for their safe use in biomedical applications. 34 Their toxicity can vary depending on several factors, including the specific type of nanocarbon ( e.g. , carbon nanotubes and graphene), dimensions ( e.g.…”
Section: Biosafety Of Carbon Nanomaterials: Crucial For Biomedical Ap...mentioning
confidence: 99%
“…• Integration with Other Technologies: Integrating CNSs with other nanotechnologies, such as nanoparticle systems or biosensors, could lead to more sophisticated drug delivery systems (Masoudi Asil et al, 2023;Saito et al, 2022).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…There had been a prime focus on nano-carbon biomaterial research and its development over the last 15 years. However, it is strongly believed that this focus would lead to paradigm shifts and lead to major advancements in global medicine by following the road towards clinical applications [80].…”
Section: Cnts Applications In the Medical Fieldmentioning
confidence: 99%